Psychometric Properties of the Malay version of Impact of Event Scale - Revised (IES-R) - Aniza, Abd Aziz; Norhayati, M.N (2014)
Introduction: Posttraumatic stress disorder may result from exposure to extreme psychological stress and the Impact of Event Scale (IES) was probably the most widely used tool used for its measurement. Aim: The objective of this study was to validate the Malay version of IES-R using a confirmatory validity approach. Methods: A cross-sectional study involving 118 women who underwent caesarian section operation in postnatal ward, Universiti Sains Malaysia Hospital was conducted. Construct validity and internal consistency was performed after the translation, content validity and face validity process. The data was analyzed using Statistical Packages for the Social Sciences (SPSS) version 20 and Analysis of Moment Structure version 18. Results: The final model which consists of three constructs with 10 items demonstrated acceptable factor loadings, domain to domain correlation and best fit; (RMSEA=0.079, GFI=0.913, CFI=0.948, TLI=0.927, x2/df=1.697). Composite Reliability and Average Variance Extracted of the domains ranged from 0.654 to 0.847 and 0.500 to 0.827 respectively. Internal consistency reliability ranged from 0.605 to 0.845. Conclusion: The study suggested that the three factor model with 10 items of the Malay version of IES-R was acceptable to be used to measure Posttraumatic stress disorder because it is valid, reliable and simple.